Single-Cell RNA Sequencing With Combined Use of Bulk RNA Sequencing to Reveal Cell Heterogeneity and Molecular Changes at Acute Stage of Ischemic Stroke in Mouse Cortex Penumbra Area - Guo, Kang; Luo, Jianing; Feng, Dayun; Wu, Lin; Wang, Xin; Xia, Li; Tao, Kai; Wu, Xun; Cui, Wenxing; He, Yixuan; Wang, Bing; Zhao, Zhenwei; et al. (Frontiers in Cell and Developmental Biology, 2021)
Stroke has been the leading cause of adult mortality and morbidity over the past several years. After ischemic stroke attack, a large number of dormant or reversibly brain cells exist in the penumbra area. However, pathological processes and unique cell information in the penumbra area under acute ischemic stroke condition still remained elusive. To investigate the heterogeneity of each cell type in the early stages of ischemic stroke and to detect early possible therapeutic targets that helping cell survival, we applied unbiased single cell sequencing in combination with bulk RNA-seq analysis together to study mouse brain penumbra area during this phase. Our results reveal the impacts of ischemic stroke on specific genes and pathways of cell types, and alter the cell trajectory differentiation of each cell type, suggesting potential functional mechanisms and therapeutic targets. Except for classical gene markers, single cell genomics demonstrate unique information of subcluster of these cell types and metabolism changes under ischemic stroke, suggesting that Gadd45b in microglia, Cyr61 in astrocytes, and Sgk3 in oligodendrocytes may play a subcluster-specific role in cell death and survival at the early stages of ischemic stroke. Meanwhile, RNA-scope multiplex in situ hybridization and immunofluorescence staining were applied for selected target gene marker to validate and confirm the existence of these cell subtypes and molecular changes during acute stage of ischemic stroke.